Electrochemical Determination of Bisphenol A at Carbon Nanotube-Doped Titania-Nafion Composite Modified Electrode - Kim, Byung Kun; Kim, Ji Yeon; Kim, Dong-Hwan; Choi, Han Nim; Lee, Won-Yong (Bulletin of the Korean Chemical Society, 2013)
A highly sensitive electrochemical detection method for bisphenol A (BPA) has been developed by using multi-walled carbon nanotube (CNT)-doped titania-Nafion composite modified glassy carbon (GC) electrode. The CNT−titania−Nafion/GC electrode exhibited excellent electrocatalytic activity towards BPA. Therefore, the CNT−titania−Nafion/GC electrode showed improved voltammetric responses for BPA compared to that obtained with bare GC electrode. In addition, cetyltrimethylammonium bromide (CTAB), a cationic surfactant, was added into the BPA sample solution in order to accumulate BPA through hydrophobic interaction between CTAB and BPA. The CNT−titania−Nafion/GC electrode gave a linear response (r2 = 0.999) for BPA from 1.0 × 10−8 M to 5.0 × 10−6 M with a detection limit of 9.0 × 10−10 M (S/N = 3). The modified electrode showed good selectivity against interfering species and also exhibited good reproducibility. The present electrochemical sensor based on the CNT–titania–Nafion/GC electrode was applied to the determination of BPA in food package samples. KCI Citation Count: 14